The Pengembangan Bahan Ajar Flipbook Matematika berbasis Problem Based Learning pada Siswa Kelas 5 Sekolah Dasar - Kosala, Aji Zuhdan; Listyaningrum, Riska; Murti, Noi Syana Daru; Dewani, Marsya Risqy; Novianto, Anwar (Universitas Sarjanawiyata Tamansiswa, 2025)
Conventional learning using limited teaching materials is still a problem that occurs in elementary school teachers today. The purpose of this development research is to produce interesting teaching material products, especially in mathematics lessons on processing and presenting data. This research is a development research using the ADDIE model, which consists of (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation.The data collection techniques used are interviews, questionnaires, and observations. The data obtained in the study were then analyzed descriptively quantitatively and qualitatively. The subjects of this study were 19 fifth grade students of SDN Jarakan. Based on the results of the study, the validation test from material experts scored 85.33% and media experts 93.33%. Meanwhile, the results of the trial from students received a score of 89% and teachers 98%. Thus, it can be concluded that this flipbook teaching material is very feasible to use to support the learning process of student.